Dynamic fiscal competition with public infrastructure investment : austerity and attracting capital inflow - Chen, Yang (2020)
In a global economy characterised by austerity, regionalisation and bidding for mobile capital, fiscal competition models have a major contribution to make to the economic development debate. With labour proving immobile, even within borderless regions like the European Union, our extension of static models into a dynamic setting offers invaluable advice for policymakers. This paper presents the effects of fiscal competition, considering the inter-temporal interactions among the economic activity of firms, capital taxation and public infrastructure investment in a small-open economy. Four cases emerge, but most interestingly public and private capital being substitutes allows reductions in the net tax burden alongside infrastructure accumulation provided public capital is not too productive. We also review factor complementarity, where subsidies become attractive. Transitional impacts depend on the marginal product of public capital. Hence, from the first case, our model addresses the apparent puzzle of high infrastructure accompanying low taxation, and does so without imposing limitations on competition.